Financial Management Strategies: Exploring the Nexus between Budget Allocation, Investment Policies, and Firm Performance - PA Andiena Nindya Putri; Upik Djaniar; Ansir Launtu; Mutmainah; Pandu Adi Cakranegara (Dinasti Publisher, 2024)
In the contemporary business landscape, effective financial management strategies play a pivotal role in determining the success and sustainability of firms. This article delves into the intricate relationship between budget allocation, investment policies, and firm performance. Budget allocation serves as a fundamental aspect of financial management, influencing resource distribution across various organizational functions. The efficacy of budget allocation strategies directly impacts the financial health and operational efficiency of firms. Moreover, investment policies represent critical decisions that shape the allocation of financial resources towards diverse investment avenues. The alignment between investment policies and organizational objectives is imperative for optimizing returns and mitigating risks. By examining the interplay between budget allocation and investment policies, this study aims to elucidate their combined impact on firm performance. Furthermore, firm performance serves as a comprehensive measure of organizational success, encompassing financial indicators, market position, and operational effectiveness. The integration of prudent budget allocation practices and strategic investment policies fosters sustainable growth and enhances competitive advantage, thereby augmenting overall firm performance. Through empirical analysis and theoretical frameworks, this article elucidates the synergistic relationship between budget allocation, investment policies, and firm performance. Insights derived from this study offer valuable implications for financial managers, policymakers, and stakeholders seeking to optimize financial management strategies in dynamic business environments.